Chloroquine and COVID-19: Should We Care about Ototoxicity? - Monteiro, Eduardo Machado Rossi; Nascimento, Maria Fernanda Lima; Brito, Thayanne Rachel Cangussu; Lima, Marcos Correia; Sefair, Laura Rodrigues; Pedrosa, Maisa Mendes (International Archives of Otorhinolaryngology, 2020)
Introduction Severe acute respiratory syndrome coronavirus 2 was first described in December 2019 in China leading to a Public Health Emergency of International Concern. It was named by the World Health Organization as Coronavirus Disease 2019 (COVID-19), and it garnered unprecedented attention from public health researchers around the world, and studies analyzing chloroquine and hydroxychloroquine as a possible therapy have arisen in the last 2 months.Objective To review the literature and describe updated facts about the ototoxicity of chloroquine and hydroxychloroquine, an important side effect that can be present in patients with COVID-19 treated with these drugs.Data Synthesis The most typical treatment regimen is 5 days of hydroxychloroquine at daily doses of 400 to 600 mg. There is no randomized clinical trial that can prove so far the efficacy of this medication, and few studies have evaluated adverse events potentially linked to their use in patients with COVID-19. While there is no concrete evidence on the incidence of ototoxicity using chloroquine in the short term, we need to consider that, as a pandemic disease, millions of patients with COVID-19 may receive this treatment, and ototoxicity can be a possible adverse event.Conclusion Despite the urgent global situation caused by the COVID-19, the risk of irreversible hearing loss may outweigh the unproven benefit of using hydroxychloroquine or chloroquine, especially in patients with mild forms of COVID-19, who may be cured with supportive treatment. The potential hearing loss that can be caused by these medications may advise against their use in COVID-19 patients.
Keywords: ototoxicity; hearing loss; COVID-19; hydroxychloroquine; chloroquine